2013
DOI: 10.1002/aic.14052
|View full text |Cite
|
Sign up to set email alerts
|

Rheological evolution and crystallization response of molten coal ash slag at high temperatures

Abstract: Ash-related problems are often the main reason for entrained-flow gasifiers and boilers unscheduled shut downs. Thus, understanding the high-temperature physical properties of molten coal ash slag may enable an accurate description of the condition of ash deposition in the gasifier and boiler. The evolution of the time dependence of rheological behaviors, including the viscosity and yield stress of the molten coal ash slag containing 0-35.51 vol % crystals at decreasing temperatures (1400-1280 C) and within 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…[19] Another reason of the shear thinning in silicate systems is the disruption of aggregates or the solid network. As reported in literature, with increasing solid fraction, solid aggregates or an internal network can form [10,23,68,69,76] . Due to the weak attraction force between particles, the aggregates or network can be broken up into isolated particles when subjected to an increasing shear rate.…”
Section: Shear-dependent Behaviorsupporting
confidence: 58%
“…[19] Another reason of the shear thinning in silicate systems is the disruption of aggregates or the solid network. As reported in literature, with increasing solid fraction, solid aggregates or an internal network can form [10,23,68,69,76] . Due to the weak attraction force between particles, the aggregates or network can be broken up into isolated particles when subjected to an increasing shear rate.…”
Section: Shear-dependent Behaviorsupporting
confidence: 58%
“…Slag samples were quenched periodically and removed for study using SEM analysis. They noted changes in molten slag viscosity as a function of temperature and crystal size distribution, and reported that transition from Newtonian to non-Newtonian flow occurs around 5% (volume/volume) solid phase content in the slag [52].…”
Section: High-temperature Rotary Viscometrymentioning
confidence: 98%
“…Mueller et al investigated the effect of particle shape on the effective viscosity using model particles suspended in silicone oil, and found that particle jamming effects can be described by R [51]. Song et al note that the Einstein-Roscoe model does not account for shear rate dependence, and proposed the use of a modified semi-empirical model that incorporates high-and low-shear rate viscosity values instead [52].…”
Section: Viscosity Of Subliquidus Molten Silicatesmentioning
confidence: 98%
See 1 more Smart Citation
“…(1) Disruption of aggregates or solid network According to this theory, the connections between crystals inside aggregates and solid network are weak and can be gradually broken up into isolated particles when the slag is subjected to a sufficient shear rate [7,[10][11][12][13] . Because of the wholly or partially disrupted microstructure, the obstruction exerted on the rotational spindle reduces, leading to a viscosity decrease.…”
Section: Shear-dependent Behaviormentioning
confidence: 99%